Effect of skiing speed on ski and pole forces in cross-country skiing - Vähäsöyrinki, P.; Komi, P. V.; Seppälä, S.; Ishikawa, M.; Kolehmainen, V.; Salmi, J. A.; Linnamo, V. (Medicine & Science in Sports & Exercise, 2008)
Purpose: The present study characterized pole and ski forces in classical technique cross-country skiing. Eight elite junior cross-country skiers performed diagonal skiing at 65%, 75%, 90%, and 100% of maximum speed on a stable 100-m-low uphill (2.5°).